M. BERDYAEV ABOUT THE PROBLEM OF REVOLUTION IN THE CREATIVE WORK OF F. DOSTOYEVSKY AND L. TOLSTOY - Попков, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article is on study the experience of N. Berdyaev’s comprehension such aspect in creative work of F. Dostoevsky and L. Tolstoy, as attitude to the problem of revolution.